Spatially dependent four-wave mixing in semiconductor quantum wells - Zhang, Yufeng; Wang, Zhiping; Qiu, Jing; Hong, Yin; Yu, Benli (Applied physics letters, 2019)
We propose a scheme to generate spatially dependent four-wave mixing (FWM) in an asymmetric semiconductor three-coupled-quantum-well nanostructure. By adjusting the detuning of the control field, one can effectively manipulate the FWM output field. Specifically, the vortex phase of the FWM field can be modulated. The detailed explanations based on the dispersion relation are given, which are in good agreement with our results. Furthermore, we perform the interference between the FWM field and the same-frequency Gaussian beam. Our results show that the interference patterns can also be modulated via the detuning of the control field, which may provide a way to observe helical phase modulation via the intensity measurement. This work may be useful for investigating the nonlinear optical phenomena based on orbital angular momentum light.